Analysis of the Moral Values of the One Piece Anime Movie "Z" And Movie ‘’Stampede’’ - Ira Maisarah; -, Ahmad Nofrian (Journal of English for Specific Purposes in Indonesia, 2024)
A movie is a type of literary work to entertain and convey a value or message to the viewer. The movie strives to communicate moral values, which are considered positive attitudes that could be adopted by everyone. This study aims to identify and analyze the moral values contained in the one-piece anime movies "Z" and "Stampede”. This study uses a grounded theory approach to the descriptive-qualitative method and analyze the moral values in the movies by using Sulistiyani’s moral theories. This study focuses on analyzing two anime films from the One Piece series, namely Z and Stampede. This research findings shows that numerous morals can drive and teach us as viewers. The morals found in the movies are courage, self-sacrifice, honesty, justice, wisdom, respect and appreciation, hard work, fulfilling promises, supporting others, and working together. Unfortunately, belief in God's values is not found in these movies since the themes of these movies are action, adventure, and, most significantly, friendship. Moreover, the moral values mostly delivered in these movies are helping others. Finally, the researcher suggests that the viewers not only derive enjoyment from the movie's plot but also apply its moral values to enhance their own character to become better individuals.